Topological design using multivariate laminate stackings for tailored fiber placement. (June 2022) - Schwingel, Johannes; Middendorf, Peter
In structural optimization of fiber-reinforced composites, unidirectional design material is normally applied due to its high anisotropy character. Using volume constraints to save weight often results in truss-like frameworks with defined tension and shear loaded areas, while the latter one is often neglected or improperly described with unidirectional material. Here, a method is proposed to extend the material design space to a continuously variable domain between UD and cross-ply laminates which is simultaneously optimized with topology. This allowed us to increase the design improvement and create smoother material distributions which is more beneficial for fiber placement technologies such as Tailored Fiber Placement. Parameter studies have been performed to investigate the effects of variable shear properties and different design spaces on the structural performance of the final designs, concluding with classical benchmarks to validate the proposed method.